2018
DOI: 10.1021/jacs.8b00665
|View full text |Cite
|
Sign up to set email alerts
|

Half-Sandwich Ruthenium Carbene Complexes Linktrans-Hydrogenation andgem-Hydrogenation of Internal Alkynes

Abstract: The hydrogenation of internal alkynes with [Cp*Ru]-based catalysts is distinguished by an unorthodox stereochemical course in that E-alkenes are formed by trans-delivery of the two H atoms of H. A combined experimental and computational study now provides a comprehensive mechanistic picture: a metallacyclopropene (η-vinyl complex) is primarily formed, which either evolves into the E-alkene via a concerted process or reacts to give a half-sandwich ruthenium carbene; in this case, one of the C atoms of the start… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
158
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 124 publications
(175 citation statements)
references
References 191 publications
(110 reference statements)
9
158
1
Order By: Relevance
“…Even the stereo‐complementary formation of Z ‐alkenes by canonical Lindlar‐type reduction, however, still faces considerable and in part unsolved problems when polyfunctional substrates need to be addressed . Although these challenges were ultimately mastered and a robust entry into callyspongiolide was established, this total synthesis project revealed significant gaps in methodological coverage and inspires investigations into better catalysts for stereoselective alkyne semi‐reduction . Work along these lines is underway in our laboratory.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Even the stereo‐complementary formation of Z ‐alkenes by canonical Lindlar‐type reduction, however, still faces considerable and in part unsolved problems when polyfunctional substrates need to be addressed . Although these challenges were ultimately mastered and a robust entry into callyspongiolide was established, this total synthesis project revealed significant gaps in methodological coverage and inspires investigations into better catalysts for stereoselective alkyne semi‐reduction . Work along these lines is underway in our laboratory.…”
Section: Resultsmentioning
confidence: 99%
“…[14] Although these challenges were ultimately mastered and ar obust entry into callyspongiolide was established, this total synthesis project revealed significant gaps in methodological coverage and inspires investigations into better catalysts for stereoselective alkyne semi-reduction. [49] Work along thesel ines is underway in our laboratory.…”
Section: Ynoatemetathesis and Completion Of The Totalsynthesismentioning
confidence: 99%
“…Of the different hydrometalation reactions investigated, trans ‐hydrostannation proved to be most receptive to this effect . In any case, compounds of type C provide many opportunities for downstream functionalization, as witnessed by a growing number of applications to target‐ and/or diversity‐oriented synthesis …”
Section: Introductionmentioning
confidence: 99%
“…Our recent studies on ruthenium catalyzed trans-hydrogenation [1,2] and trans-hydrometalation [1,[3][4][5] reactions showed that internal alkyneso ft ype A bearingaprotic substituent at the propargylic positiona re privileged substrates (Scheme 1). [6][7][8][9] Ample experimental and computational evidence suggests that an incipient hydrogen bond between the -XH group (X = O, NR) and the polarized [Ru-Cl] entity of the catalyst favors substrate binding. [6,7,10] Moreover,t his inter-ligand interaction imposes directionality on the loaded complex B and the ensuing transition state, which explains the generally excellent levels of regio-and stereoselectivity in favor of the a/transproduct C.O ft he different hydrometalation reactions investigated, trans-hydrostannation provedt ob em ost receptive to this effect.…”
Section: Introductionmentioning
confidence: 99%
“…It is noteworthy that only the ruthenium-catalyzed hydroboration shows this massive switch from the trans-t oacis-addition mode upon increase of the size of one substituent on the triple bond, whereas the other alkyne hydroelementations catalyzedb y[ Cp*RuCl] are hardly responsive: [25][26][27][28][29][30][31] The comparison with the hydrostannation of 33 with formation of 35 illustrates this aspect, [31] which remains trans-selective and is therefore complementary to the hydroboration of this substrateinregio-as well as stereochemical terms. Given the remarkable mechanistic congruenceo f the reactionp athways for either transformation,w hich have been subject to DFT studies in the past, [13,23,31,50] the origins of this divergent behaviora re uncleara nd subject to ongoing investigationsino ur laboratory.…”
mentioning
confidence: 99%